Retinal microglia express more MHC class I and promote greater T-cell-driven inflammation than brain microglia - Bloomfield, Christina L.; Gong, Joyce; Droho, Steven; Makinde, Hadijat M.; Gurra, Miranda G.; Stumpf, Cecilia H.; Kharel, Arjun; Gadhvi, Gaurav; Winter, Deborah R.; Cui, Weiguo; Cuda, Carla M.; Lavine, Jeremy A. (Frontiers in Immunology, 2024)
Macrophage function is determined by microenvironment and origin. Brain and retinal microglia are both derived from yolk sac progenitors, yet their microenvironments differ. Utilizing single-cell RNA sequencing (scRNA-seq) data from mice, we tested the hypothesis that retinal and brain microglia exhibit distinct transcriptional profiles due to their unique microenvironments. Eyes and brains from 2-4 month wildtype mice were combined (20 eyes; 3 brains) to yield one biologically diverse sample per organ. Each tissue was digested into single cell suspensions, enriched for immune cells, and sorted for scRNA-seq. Analysis was performed in Seurat v3 including clustering, integration, and differential expression. Multi-parameter flow cytometry was used for validation of scRNA-seq results. Lymphocytic choriomeningitis virus (LCMV) Clone 13, which produces a systemic, chronic, and neurotropic infection, was used to validate scRNA-seq and flow cytometry results in vivo. Cluster analysis of integrated gene expression data from eye and brain identified 6 Tmem119 + P2ry12 + microglial clusters. Differential expression analysis revealed that eye microglia were enriched for more pro-inflammatory processes including antigen processing via MHC class I (14.0-fold, H2-D1 and H2-K1) and positive regulation of T-cell immunity (8.4-fold) compared to brain microglia. Multiparameter flow cytometry confirmed that retinal microglia expressed 3.2-fold greater H2-Db and 263.3-fold more H2-Kb than brain microglia. On Day 13 and 29 after LCMV infection, CD8 + T-cell density was greater in the retina than the brain. Our data demonstrate that the microenvironment of retina and brain differs, resulting in microglia-specific gene expression changes. Specifically, retinal microglia express greater MHC class I by scRNA-seq and multi-parameter flow cytometry, resulting in a possibly enhanced capability to stimulate CD8 + T-cell inflammation during LCMV infection. These results may explain tissue-specific differences between retina and brain during systemic viral infections and CD8 + T-cell driven autoimmune disease.